Multidetector computed tomography findings in a case of top of basilar syndrome (Indian Journal of Case Reports, 2018)
Stroke is a condition in which poor blood flow to the brain results in cell death. In India, almost 2,00,000 strokes are reported a year. Basilar artery occlusion syndrome accounts for 1–4% of all strokes. Top of the basilar syndrome is a type of basilar artery occlusion syndrome where the distal end of the basilar artery is occluded. Imaging findings include ischemic changes in the areas supplied by the distal branches of the basilar artery. A posterior circulation - acute stroke prognosis early computed tomography score system can be used to evaluate the prognosis of the patient. We are reporting a case of top of the basilar syndrome in an 85-years-old female patient who presented to us with complaints of one episode of seizure.